Path independence of the additive functionals for McKean–Vlasov stochastic differential equations with jumps - Jiang-lun Wu (Infinite Dimensional Analysis, Quantum Probability and Related Topics, 2021)
In this article, the path independent property of additive functionals of McKean-Vlasov stochastic differential equations with jumps is characterised by nonlinear partial integro-differential equations involving L-derivatives with respect to probability measures introduced by P.-L. Lions. Our result extends the recent work [16] by Ren and Wang where their concerned McKean-Vlasov stochastic differential equations are driven by Brownian motion.